2023
DOI: 10.1101/2023.04.21.537811
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

The effect of developmental variation on expression QTLs in a multi parentalC. eleganspopulation

Abstract: Regulation of gene expression plays a crucial role in the development and adaptation of organisms to changing environments. A population-based procedure used to investigate the genetic regulation of gene expression is eQTL mapping. Typically, the age of the population used for eQTL mapping at the time of sampling is strictly controlled. This is necessary because the developmental process causes changes in gene expression, complicating the interpretation of eQTL mapping experiments. However, organisms can diffe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(3 citation statements)
references
References 43 publications
0
3
0
Order By: Relevance
“…The identification of ERECTA as the most likely causal gene for a hotspot on chromosome 2 in use case 2 shows the power of prior knowledge-based prioritization of master regulators. However, it was recently shown that eQTL hotspots could arise due to variation in developmental age within the tested population (van Eijnatten et al 2023;Francesconi and Lehner 2014), batch effect (Michaelson et al 2009), or be attributed to the formation of specific plant tissues (Vosman et al 2019). In such cases, it might be more fruitful to look for commonalities between the target genes since the connection to the actual regulator can involve many regulatory steps, while analysis of the target genes could point to an underlying phenomenon.…”
Section: Chaptermentioning
confidence: 99%
See 2 more Smart Citations
“…The identification of ERECTA as the most likely causal gene for a hotspot on chromosome 2 in use case 2 shows the power of prior knowledge-based prioritization of master regulators. However, it was recently shown that eQTL hotspots could arise due to variation in developmental age within the tested population (van Eijnatten et al 2023;Francesconi and Lehner 2014), batch effect (Michaelson et al 2009), or be attributed to the formation of specific plant tissues (Vosman et al 2019). In such cases, it might be more fruitful to look for commonalities between the target genes since the connection to the actual regulator can involve many regulatory steps, while analysis of the target genes could point to an underlying phenomenon.…”
Section: Chaptermentioning
confidence: 99%
“…In such cases, it might be more fruitful to look for commonalities between the target genes since the connection to the actual regulator can involve many regulatory steps, while analysis of the target genes could point to an underlying phenomenon. The simplest way is to analyse the GO term or pathway enrichment to identify gene expression co-founder (as in (van Eijnatten et al 2023)), which at the same time can help identify the characteristics of the causal genes based on functional annotations. This feature should be the focus of future development.…”
Section: Chaptermentioning
confidence: 99%
See 1 more Smart Citation